Description of a new species of genus Gobio from Turkey (Teleostei: Cyprinidae) - Turan, Davut; Ekmekçi, F. Güler; Luskova, Vera; Mendel, Jan (Zootaxa, 2012)
Gobio sakaryaensis, a new species from the Tozman and the Porsuk streams of the Sakarya River drainage (northwesternAnatolia, Black Sea basin), is described. The species is distinguished from other gudgeons by a combination of the fol-lowing characters: breast completely scaled, scales approximately extending to isthmus; head length 27.2–30.0 % SL; 39–42 lateral line scales; 4–6 scales between anus and anal-fin origin; 6–8 scales between posterior extremity of pelvic-fin bases and anus. A key is provided for Gobio and Romanogobio species recorded from Turkey.